Invasive mosquito species Aedes albopictus and Aedes aegypti on the Black Sea coast of the Caucasus: genetics (COI, ITS2), Wolbachia and Dirofilaria infections - E. V. Shaikevich; I. V. Patraman; A. S. Bogacheva; V. М. Rakova; O. Р. Zelya; L. A. Ganushkina (Вавиловский журнал генетики и селекции)
The area of invasive species Aedes albopictus and Aedes aegypti is expanding. Precise identification and understanding of the genetic diversity of invasive mosquito populations allows us to develop appropriate control methods. Endosymbiotic bacterium Wolbachia pipientis has different effects on their arthropod hosts and can influence the transmission and spread of the pathogens. The objective of the presented study was molecular-genetic identification of the Aedes mosquitoes collected in sampling sites on the Black Sea coast from 2007 to 2017; determination of genetic variability of Ae. aegypti, Ae. albopictus and their symbiotic bacteria Wolbachia; assessment of mosquitoes ability to be infected and to spread parasitic Dirofilaria. Another objective was obtaining the genetic characteristic of laboratory strain Ae. aegypti IMPITM. We investigated two markers of nuclear and mitochondrial DNA from Ae. albopictus and Ae. aegypti and compared them to DNA from Ae. cretinus and Ae. koreiсus sympatrically inhabiting the territory, as well as to one of Ae. aegypti from a laboratory line. The study of nuclear and mitochondrial DNA revealed a low level of variability in the invasive mosquitoes Ae. albopictus and Ae. aegypti collected at different collection sites and in different years. More than a half of Ae. albopictus were infected with Wolbachia, two strains of bacteria, wAlbA and wAlbB, occur in the Ae. albopictus population on the Black Sea coast. Total infection of Ae. aegypti and Ae. albopictus with dirofilariae was 1.8 %. Dirofilaria immitis was found only in mosquito abdomen, larvae of infective stage L3 were not found. D. repens larvae developed to the infective stage in the mosquitoes of both species.